Sete Fontes: a challenge to promote the heritage legacy and facing water sources scarcity in the city of Braga-Portugal - Vieira, J. M. Pereira (2016)
An ancient drinking water supply system, called Sete Fontes (Seven Springs), was built in the mid-eighteenth century in the city of Braga. The system is composed by underground galleries, cisterns, waterspouts, fountains, and (covered) stone aqueduct channels with about 3500 m long. This national monument, still existing and active, preserves both the original memorial role (representative of a boost to urban and baroque architecture), and the original function (improvement of quality of life), being a witness of the evolution of hydraulic engineering concepts, which greatly contributed to the improvement of urban infrastructures and the protection of public health. This paper also presents an overview of the history of the water supply system of the city of Braga, from the Roman period to the contemporary age, with special focus on Sete Fontes water sources characterization (morphological, hydrogeological, hydraulic, and water quality). This heritage legacy is invaluable not only for its history and cultural significance, while maintaining its authenticity and integrity, but also due to its confirmed water quality that can be an added value, taking a new relevance to address future scarcity scenarios of safe water sources in a climate change context.